2011
DOI: 10.2172/1019027
|View full text |Cite
|
Sign up to set email alerts
|

Melter Off-Gas Flammability Assessment for DWPF Alternate Reductant Flowsheet Options

Abstract: EXECUTIVE SUMMARYGlycolic acid and sugar are being considered as potential candidates to substitute for much of the formic acid currently being added to the DWPF melter feed as a reductant. A series of small-scale melter tests were conducted at the Vitreous State Laboratory (VSL) in January 2011 to collect necessary data for the scoping assessment of the impact of these alternate reductants on the melter off-gas flammability. The resulting data were analyzed in this work with the aid of modeling and re-baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…SRNL has conducted process testing to support the change in the alternate reductant from formic acid to glycolic acid [4,7], evaluated the impact on some downstream facilities' processes [8,9,32], as well as modeled the melter off gas stream for destruction of glycolic acid [10]. From these investigations the following points were highlighted for further evaluation:…”
Section: Previous Testing and Evaluationsmentioning
confidence: 99%
“…SRNL has conducted process testing to support the change in the alternate reductant from formic acid to glycolic acid [4,7], evaluated the impact on some downstream facilities' processes [8,9,32], as well as modeled the melter off gas stream for destruction of glycolic acid [10]. From these investigations the following points were highlighted for further evaluation:…”
Section: Previous Testing and Evaluationsmentioning
confidence: 99%
“…They indicated Y(OH) 3 and Zr(OH) 4 precipitate in the absence of glycolate. Wang et al 48 used sodium glycolate to dissolve antimony(III) acetate.…”
Section: Lu and Iglesiamentioning
confidence: 99%
“…The ion exchange resin in the previous step is regenerated (i.e, cesium and strontium removal from the resin) to allow it to be reused using 2M NaNO 3 .…”
Section: Ion Exchange Resin Regenerationmentioning
confidence: 99%
“…The DM10-SB6 data were actually analyzed earlier to support the down-select and reanalyzed here with an emphasis on the impact of melter design on the data. 27 Efforts were again made to achieve as low a vapor space temperature as practically possible, as was done during the DM10-A2 run. However, instead of overfeeding, the DM10 vapor space was cooled this time by introducing ambient air directly into the vapor space, while maintaining a constant feed rate; therefore, it was presumed to be non-disruptive to the steady state operation.…”
Section: Dm10-sb6 Runmentioning
confidence: 99%
“…The melter off-gas flammability assessment performed earlier in support of the down-select process indicated that a significant fraction of glycolic acid added might remain undissociated and volatilize upon entering the melter, ending up in the condensate recycle to the Tank Farms. 2 Hence, it is also of vital importance to analyze the off-gas condensate produced during the test for the presence of glycolate or any other organic species that may pose operational difficulties on the downstream processes.…”
Section: Introductionmentioning
confidence: 99%